TEAM TEACHING MODELS AND PRIMARY SCHOOL PUPILS’ LEARNING OUTCOMES IN MATHEMATICS IN OYO, NIGERIA (2019)
Mathematics is taught at the primary schools to enable pupils apply its skills to solve daily problems. There is evidence that pupils have phobia for and poor performance in Mathematics. This has been attributed to teachers’ non-use of effective teaching methods such as the team teaching models. Previous studies have focused largely on individual teaching methods with little attention paid to the use of Collaborative Team Teaching (CTT) and Alternative Team Teaching (ATT) models in improving pupils’ learning outcomes in Mathematics. The study, therefore, was designed to investigate the effects of CTT and ATT on pupils’ Achievement in Mathematics (AM), Interest in Mathematics (IM) and Dexterity in Mathematics (DM). The moderation effects of Pupils’ Learning Styles (PLS) and Pupils’ Self-efficacy (PS) were also examined. Tuckman’s Team and Activity Learning theories served as the framework. Explanatory sequential mixed methods design (QUAN qual) with dominant quantitative component (QUAN-dominant) was adopted in the study, while the quantitative aspect used 3x3x3 factorial matrix. Both simple random and homogenous purposive sampling techniques were used. Simple random sampling technique was used to select three Local Government Areas (LGAs) in Oyo. From each LGA, three public primary schools were randomly selected and an intact class of primary V pupils was adopted from each school. The classes were assigned to CTT (143), ATT (129) and control (129) groups, while treatment lasted for five weeks. Homogenous purposive sampling method was used to select 72 pupils, 12 primary five Mathematics teachers and 6 head teachers. Instruments used were AM (r=0.78) and DM (r=0.82) tests; IM (α=0.87), PLS (α=0.84) and Mathematics Self-efficacy (α=0.82) scales and instructional guides. These were complemented with 12 focus group discussions with pupils and 18 in-depth interview sessions with six headmasters and 12 Primary V Mathematics teachers. Data were analysed using Analysis of covariance, Sidak post-hoc test at 0.05 level of significance, while qualitative data were content-analysed. There were significant main effects of treatment on AM (F(2,374)=62.85, partial ɳ2=0.25) and IM (F(2,374)=29.86, partial ɳ2=0.14) but none on DM. Pupils in the ATT (21.09) had the highest mean score in AM, followed by pupils in CTT (12.13) and control (9.84) groups. Pupils in ATT (42.82) had the highest mean score in IM, followed by pupils in control (28.15) and CTT (27.83). There was no significant main effect of PLS on AM, IM and DM. The PS had no significant main effect on AM, IM and DM. The two-way and three-way interaction effects were not significant. Collaborative and alternative team teaching models made learning easier; provided clear understanding of the content; enhanced close interaction between pupils and teachers; and engendered innovation and creativity. Challenges associated with collaborative and alternative team teaching models included inferiority or superiority complex and conflicts among teachers. Solutions to the challenges were planning, monitoring, supervision, communication and mutual understanding. Both collaborative and alternative team teaching models improved pupils’ achievement in mathematics, while only alternative team teaching model aroused pupils’ interest in Mathematics. Primary school teachers should employ these models in teaching mathematics.